Optical and Kinetic Art - Compton, Michael (London : Tate Gallery, 1967)
Soto, Jesus-Raphael ; Vasarely, Victor ; Albers, Josef ; Riley, Bridget ; Yvaral, Jean-Pierre ; Fuller, Sue ; Kidner, Michael ; Olson, Eric ; Gabo, Naum ; Martin, Kenneth ; Sedgley, Peter ; Martin, Mary ; Sobrino, Francisco ; Uecker, Gunther ; Mack, Heinz ; etc.
Engels
boek